Comparison of the effects of mixed tempeh with soy tempeh on cognitive function in older people - Turana, Yuda; Handajani, Yvonne Suzy; Barus, Tati; Kristian, Kevin; Theodoraliu, Elvina; Suswanti, Ika (Frontiers in Nutrition, 2025)
IntroductionAntioxidants may help alleviate cognitive impairment in older adults, which is often caused by oxidative stress. This research focuses on developing tempeh enriched with antioxidant-rich ingredients, including sunflower seeds, pumpkin seeds, and adzuki beans, to enhance its neuroprotective properties. This study is the first to investigate the effectiveness of mixed tempeh in reducing cognitive decline.MethodsThis experimental study (a non-randomized controlled trial) included 57 older participants with mild cognitive impairment who did not have diabetes. The participants were divided into two groups: one consumed mixed tempeh (comprising sunflower seeds, pumpkin seeds, adzuki beans, and regular soybeans), while the other group consumed soy tempeh. Both groups were instructed to consume 100 g daily over a period of 4 months and to avoid other fermented foods. Cognitive assessments were conducted before and after the intervention to evaluate the effects of tempeh consumption.ResultsThe majority of participants were female (68.4%), aged over 65 years (77.2%), and had an education level of 12 years or more (59.6%). The mixed tempeh group showed improvement in three cognitive domains (global cognitive, memory, and verbal fluency) before and after the intervention, while the soy tempeh group experienced improvements in two domains (memory and visuospatial).ConclusionThe study highlights the cognitive benefits of tempeh, particularly when mixed with other nutrient-rich ingredients. The combination of sunflower seeds, pumpkin seeds, and adzuki beans in mixed tempeh provides superior neuroprotective effects than traditional soy tempeh. This research supports the idea of promoting mixed tempeh as a healthy food alternative, especially for older adults, by offering enhanced nutritional value and cognitive health benefits.